Evaluation of Plastic Brain Response to Long-Term Exposure to Varying Habitat Complexities in Guppies (Poecilia reticulata) (2024)
Understanding how environmental complexity influences neuroanatomy and brain function is key in elucidating the adaptive mechanisms of organisms. Here, we investigate the plastic brain response of guppies (Poecilia reticulata) to long-term exposure (8 months) to varying habitat complexities. Guppies were housed in habitats with increasing spatial complexities: low (empty tank), medium (gravel and one artificial plant), and high (gravel with multiple artificial plants). After the exposure period, fish underwent spatial cognition tests to evaluate their spatial abilities and were euthanized to carry out neuroanatomical analyses. Additionally, immunohistochemistry was performed to quantify neuronal densities and understand mechanisms underlying brain plasticity. We found differences between males and females, suggesting sex-specific responses to the challenges presented by varying environmental complexities. Similarly, neuroanatomical analyses exhibited significant differences between sexes for all complexity levels, notably in males. Our findings underscore the dynamic interplay between environmental complexity and brain plasticity in guppies. By systematically assessing various aspects of brain morphology and function, we provide valuable insights into how guppy brains respond to long-term environmental complexity.